Laser Thermal Hardening - TuychiyevAbdumalikTursunovich (Zien Journals, 2022)
This article is about the most advanced types of laser technology in Mechanical Engineering and their application. This article is covered about several types and the principles of performance are explained.
Keywords: machinery; laser; technology; modern cutting machines